DIGITALIZATION OF HEALTHCARE SYSTEMS AS A DRIVER OF ORGANIZATIONAL AND SOCIAL TRANSFORMATION OF CONTEMPORARY MEDICAL PRACTICE - Karolina Jolanta Pilarska; Marta Kołodziej-Sieradz; Hubert Jarosław Ćwiek; Paulina Klaudia Gryz; Anna Aleksandra Szwankowska; Anna Baczyńska; Błażej Boruszczak; Anna Magdalena Terlecka; Adam Wiktor Rożenek; Kacper Komorowski (International Journal of Innovative Technologies in Social Science, 2026)
Digital transformation is a key process shaping contemporary medical care systems worldwide. The adoption of digital technologies, including electronic health records, telemedicine platforms, and analytics-based clinical systems, is progressively influencing organizational structures and medical practice. This review article examines healthcare digitalization as a socio-technical process that drives organizational and social transformation within contemporary healthcare systems. A structured narrative review methodology was applied to interdisciplinary literature published between 2015 and 2025, focusing on organizational change, physician professional practice, patient–physician relationships, and governance challenges associated with digital health implementation. The analysis shows that digitalization reshapes healthcare institutions by promoting data-driven management models, modifying clinical decision-making procedures, and redefining traditional professional roles. Simultaneously, digital healthcare introduces ethical, legal, and social challenges related to data protection, professional responsibility, and digital inequality. The evidence shows that successful digital transformation depends not only on technological advancement but also on organizational readiness, professional acceptance, and effective administrative frameworks. Healthcare digitalization should therefore be understood as a systemic transformation that requires the combination of technological innovation alongside social and institutional adaptation.